Relationship Between Self Control and Cyber Dating Violence In Couples Who Have Long Distance Relationships - Kudus, Desideria Mulia Mersidus; Keraf, M. K. P. Abdi; Panis, Marleny P; Junias, Marylin S (Universitas Nusa Cendana, 2023)
Emerging adulthood in romantic relationships, especially those in long distance relationships, has the possibility of cyber dating violence to occur, for this reason it is necessary to have self control in romantic relationships. This study aims to determine the relationship between self control and cyber dating violence in couples undergoing long distance relationships in Kupang City. This type of quantitative research with a correlational approach. Participants in the study were 368 women and men who had or were in a long distance relationship, aged 18-25 years. Collecting data using the Self Control Scale (Cronbach' = 0.917) which consists of 2 dimensions, namely the dimensions of inhibition and initiation; and Cyber ​​Dating Violence Scale (Cronbach' = 0.952) which consists of 2 dimensions, namely psychological violence and relational violence. Data analysis using Spearman Rank. The results of the analysis show that there is a significant relationship between self control and cyber dating violence. Keywords: Self Control, Cyber Dating Violence, Emerging Adulthood, Long Distance Relationship